2005
DOI: 10.1152/ajprenal.00172.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of Rhbg in the mouse does not impair renal ammonium excretion

Abstract: NH(4)(+) transport by the distal nephron and NH(4)(+) detoxification by the liver are critical for achieving regulation of acid-base balance and to avoid hyperammonemic hepatic encephalopathy, respectively. Therefore, it has been proposed that rhesus type B glycoprotein (Rhbg), a member of the Mep/Amt/Rh NH(3) channel superfamily, may be involved in some forms of distal tubular acidosis and congenital hyperammonemia. We have tested this hypothesis by inactivating the RHbg gene in the mouse by insertional mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 46 publications
4
70
2
Order By: Relevance
“…This channel mechanism is contrary to the early thoughts that Amt is an active transporter with capacity to concentrate NH 4 ϩ (17,18) and Rh-like Amt is an NH 4 ϩ cation transporter (19,20). Furthermore, Rh gene disruption does not alter ammonium homeostasis in slime mold (21) or renal ammonium excretion in mice (22), challenging the view that Rh proteins transport ammonium (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Thus, Rh and Amt specify two sequence-related yet substrate-distinct members of the biological gas channel family mediating diffusion of CO 2 and NH 3 , respectively.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…This channel mechanism is contrary to the early thoughts that Amt is an active transporter with capacity to concentrate NH 4 ϩ (17,18) and Rh-like Amt is an NH 4 ϩ cation transporter (19,20). Furthermore, Rh gene disruption does not alter ammonium homeostasis in slime mold (21) or renal ammonium excretion in mice (22), challenging the view that Rh proteins transport ammonium (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Thus, Rh and Amt specify two sequence-related yet substrate-distinct members of the biological gas channel family mediating diffusion of CO 2 and NH 3 , respectively.…”
mentioning
confidence: 70%
“…This redundancy may well explain the seemingly normal phenotype seen in single knockouts made in slime mold (21) and mice (22), which harbor two and four Rh genes, respectively (1,5). Our studies here demonstrate in worms that the Rh1 gene is essential and the Rh2 gene is dispensable.…”
Section: Embryonic Lethality Of Cerh1 Rnai Mutants Can Be Rescued Bymentioning
confidence: 99%
“…This suggestion was based on the basolateral location of RhBG glycoproteins, together with the observation that expressions of RhBG mRNA and protein were not increased metabolic acidosis (which results in net excretion of acid and ammonia by the mammalian renal system) (Seshadri et al, 2006). Others have reported that genetic ablation of RhBG in the knockout mice did not affect ammonia transport in the kidney and tolerance to chronic acid-loading (Chambrey et al, 2005;Chambrey et al, 2006), although other genes may have been upregulated to compensate for the Rh knockdown. RhBG expressions are restricted to kidney, liver and gastrointestinal tract in the mammals (human and mouse) Handlogten et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive in vitro evidence shows that all mammalian Rh glycoproteins, RhAG/Rhag, RhBG/Rhbg, and RhCG/Rhcg, can transport ammonia (8 -16,59) and that collecting duct ammonia transport exhibits characteristics that are consistent with transport by Rh glycoproteins (26,37). However, disruption of the Rhbg gene does not detectably alter basal or acidosis-stimulated renal ammonia metabolism (60). Therefore, either Rhbg is not involved in renal ammonia transport, or compensatory mechanisms exist in its absence.…”
Section: Discussionmentioning
confidence: 99%